Perception of social studies teachers and fourth year students on social studies instruction in Jose Abad Santos High School - Esteban, Josefa R. (1978)
The main problem of this study was to determine the perceptions of social studies teachers and fourth year students on social studies instructions in Jose Abad Santos High School, Division of City Schools, Manila. The normative-descriptive survey was used in this study. The data was gathered through the use of a questionnaire administered to 173 high school students and 25 social studies teachers. The teachers enjoyed teaching Philippine History most while the students like World History the best. The findings likewise indicated that social studies teachers were most respected of all their academic teachers and that social studies subject was their subject most studied at home. The social studies teachers knew fully well the main characteristics of the new social studies.